Comparison of American orthopedic foot and ankle society score between anterior to posterior lag screws versus posterior buttress plating for posterior malleolus fixation in tri-malleolar ankle fracture - Ali, Khandoker Muhammud Mazher; Islam, Muhammad Mozaherul; Badar Uddin, K. M.; Rukanuddawla Khan, M.; Atikur Rahman Shojib, M. (International Journal of Research in Orthopaedics, 2023)
Background: Posterior malleolar fractures are frequent, occurring in up to 44% of all ankle fractures. Surgical management typically involves anterior to posterior (AP) lag screws or posterior buttress plates. This study aimed to compare the AOFAS (American orthopedic foot and ankle society) score between AP lag screw and posterior buttress plating for posterior malleolus fixation in tri-malleolar ankle fracture. Methods: This quasi-experimental study was conducted at the department of orthopedics and traumatology, Chittagong medical college hospital, Chattogram, Bangladesh, from November 2020 to October 2021. It involved 28 patients with ankle fractures, equally divided into two groups. Group A received AP lag screw fixation, and group B underwent posterior buttress plating. Data analysis was performed using MS office tools and SPSS version 23.0. Results: The posterior plating group demonstrated superior postoperative AOFAS scores compared with the AP screw group with statistically significant differences (88 versus 81, p=0.008). Significant differences were noted in the AOFAS pain score (p=0.045) and function score (p=0.019) at the final follow-up between the two groups. Conclusions: Patients with tri-malleolar ankle fractures in whom the posterior malleolus is treated with posterior buttress plating show superior postoperative AOFAS scores at follow-up compared to those treated with AP screws.